Optimization of methane sensing response of a ZnO-graphene composite using the response surface method: sensing area and annealing temperature TEMPERATURE - Mohd Chachuli, Siti Amaniah; Sayuti, Mohamad Adzhim; Coban, Omer; Shamsudin, Nur Hazahsha (Royal Society of Chemistry, 2025)
Methane traps heat 25 times more than carbon dioxide and is highlighted as the second most potent greenhouse gas, contributing to climate change. As the methane level grows, the impact on the Earth's climate becomes more severe, and exposure to high levels can lead to adverse consequences for the human health, causing symptoms like changes in breathing and heart rate, numbness, and death in case of prolonged and high exposure. To address these concerns, this study focuses on the optimization of a ZnO-graphene composite in gas sensors for methane sensing at room temperature using the response surface method (RSM). RSM was conducted using the Design Expert 13 software by optimizing two parameters: sensing area and annealing temperature. Ten samples of ZnO-graphene gas sensors were fabricated based on the sensing layer area (1 cm2–4 cm2) and annealing temperature (100–200 °C). The ZnO-graphene gas sensor was fabricated using a screen-printing technique on a Kapton film by applying silver paste (Ag) as the interdigitated electrode and ZnO-graphene as the sensing layer. The optimization using the RSM highlighted that the experimental model was significant with an R2 value of 0.8871. Results revealed that the sensing layer area has more influence on the gas sensor sensitivity than the annealing temperature. The optimized model showed that an area of 4 cm2 and an annealing temperature of 100 °C are the optimal parameters, with a sensitivity value of approximately 0.968167 × 10−3 for 5000–7000 ppm of methane.